ANALISIS PERKEMBANGAN, KONTRIBUSI DAN EFEKTIVITAS PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN KUDUS - Nanda Asta Surya Husada, 10.05.52.0061; Maryono, Maryono (Students Journal of Accounting and Banking, 2015)
The purpose of this study is to analyze the growth of the District Revenue Holy, analyzes the development of local taxes Holy District, analyze the effectiveness of the realization of the original income of the filing of the target area Kudus years 2009-2013, analyze the effectiveness of local tax revenue to the revenue target blood Kudus years 2009-2013, analyzing the contribution of local taxes to Revenue Holy District, analyze each type of local taxes to local taxes, analyzing government policies and constraints in improving the original income. Data analysis method used is a quantitative method of research procedures which produce descriptive ie by comparing the regulations that apply to the implementation and management of the Department of Revenue in Regional District. Holy of years from 2009 to 2013. The results of the analysis of the development of the Holy Revenue District in 2009-2013 on average increased by 14.99%, the development of the local tax Kudus year on average from 2009 to 2013 increased by 33.97%, the effectiveness of local Revenue to the filing of the target area Kudus years 2009-2013 the average by 103.54% (very effective), the effectiveness of local tax revenue to the revenue target area Kudus year on average from 2009 to 2013 amounted to 109.60 % (very effective), the contribution of local taxes to Revenue District Holy year on average from 2009 to 2013 amounted to 30.50%, the contribution to the local tax perjenis smallest local taxes on average by 0.36% and the largest average 67.69, government policies and constraints Holy District local Revenue to improve the socializing Revenue to local taxpayers regarding local regulations relating to the provision of local taxes, the constraints faced by local government in improving the local tax Holy is the lack of information related to the local tax , efforts to generate revenues, which increased its revenues Holy regency field of tax and retribution areas, the results are separated areas of wealth management, other legitimate income, to explore the potential of the area, both with optimal utilization of the available resources and find the source another untapped revenues through intensive data collection. Keywords: Local Taxes, Local Revenue